Tweet!! Persidangan Burung Singapura - Aveling, Harry (Paradigma: Jurnal Kajian Budaya, 2018)
Religions have become the main topics in the novels by a prolific Singaporean author, Isa Kamari (born in 1960). His understanding and interpretation of religions have begun to develop with the writing of his first novel Satu Bumi (One Earth) in 1998. His latest novel, Tweet (2016) was influenced by an allegorical and mystical work, Persidangan Burung (Bird Conference) (c.1177). Two main narratives, one in the form of a physical nature between a grandfather and his grandson in a bird garden in Singapore and the other in the form of a spiritual nature concerning spiritual birds, ran parallel and converged at a number of important crossroads. These narratives also offered an understanding and appreciation of spirituality that could change and form life on earth in positive and integrated manners that eventually led to goodness rather than to escape from it.